Studi Kasus Pekerja CV. Batu Alam Terhadap Perspektif Mcclelland Teori Motivasi - Dhiyaul Haqqi Al-Mumtaza; Mochammad Fiki (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Employment opportunities are of course of many types, in this subject matter will take the phenomenon of Sumberwringin Village, in which there are mining activities, this mining activity is certainly a positive impact on the local community, because many think that the emergence or existence of a mine in their area will tend to help their income, this factor is what causes the community to agree to the existence of the mine. The mine, which began its activities in 2015, began to show its prestige by being recognized by other regions, in accordance with the study used, namely the existence of this new work activity can foster and increase a sense of solidarity with others and a sense of caring, not only this factor, there is a common motivation between people, namely many people whose economies are below, which makes people have the same opinion and agree to the existence of mining activities..